2020
DOI: 10.3389/fonc.2020.01389
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MDMX for Cancer Therapy: Rationale, Strategies, and Challenges

Abstract: The oncogene MDMX, also known as MDM4 is a critical negative regulator of the tumor suppressor p53 and has been implicated in the initiation and progression of human cancers. Increasing evidence indicates that MDMX is often amplified and highly expressed in human cancers, promotes cancer cell growth, and inhibits apoptosis by dampening p53-mediated transcription of its target genes. Inhibiting MDMX-p53 interaction has been found to be effective for restoring the tumor suppressor activity of p53. Therefore, MDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 135 publications
(226 reference statements)
0
33
0
Order By: Relevance
“…MDMX, as a critical negative regulator of p53 tumor suppressor, has gradually evolved into a promising cancer therapeutic target with a high similar function and structure to MDM2. 16 The abnormal expression of miRNAs and MDMX are very common in different types of human cancer. Previous studies have suggested that the expression level of MDMX is correlated to the overall survival of patients with salivary gland cancer (SGC), chronic lymphocytic leukemia (CLL), and soft tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MDMX, as a critical negative regulator of p53 tumor suppressor, has gradually evolved into a promising cancer therapeutic target with a high similar function and structure to MDM2. 16 The abnormal expression of miRNAs and MDMX are very common in different types of human cancer. Previous studies have suggested that the expression level of MDMX is correlated to the overall survival of patients with salivary gland cancer (SGC), chronic lymphocytic leukemia (CLL), and soft tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…44 Considering that blocking MDMX-p53 interaction or inhibiting MDMX expression is effective for restoring the tumor suppressor activity of p53, MDMX could be considered as one of the most promising molecular targets for developing anticancer therapeutics. 16,[45][46][47][48][49] Of course, miRNAs that regulate the MDMX-p53 pathway can also play a pivotal role in human cancer.…”
Section: The Abnormal Expression Of Mdmx In Human Cancermentioning
confidence: 99%
See 3 more Smart Citations